Recent and Prospective Adoption of Genetically Modified Cotton: A Global Computable General Equilibrium Analysis of Economic Impacts - Anderson, Kym; Valenzuela, Ernesto; Jackson, Lee Ann (2012)
This article provides estimates of the economic impact of initial adoption of genetically modified (GM) cotton and of its potential impacts beyond the few countries where it is currently common. Use is made of the latest version of the GTAP database and model. Our results suggest that if other developing countries--especially in sub-Saharan Africa--were to follow the lead of China, South Africa, and most recently India, adoption of GM cotton varieties could provide even larger proportionate gains to farmer and national welfare than in those early-adopting countries. Furthermore, those estimated gains are shown to exceed--and reinforce--those from a successful campaign under the WTO's Doha Development Agenda to reduce/remove cotton subsidies and import tariffs globally.